Courts' inquiry into arbitral jurisdiction at the pre-award stage : a comparative analysis of the english, German and swiss legal order - Synkova, Sandra (Springer International Publishing, 2013)
International arbitration has become the favored method of resolving disputes between business partners in almost every aspect of international trade, commerce, and investment. The resolution of a dispute by means of international arbitration provides the parties with an opportunity to resolve their disputes in a private, confidential, cost and time efficient manner before a neutral tribunal of their choice. However, challenges to arbitral jurisdiction have become a common practice in the field. Resolution of such challenges may significantly delay the resolution of the parties' primary substantive dispute, increase overall dispute resolution costs and even whittle down the benefits of the parties' bargain to arbitrate. Accordingly, adopting a proper approach to the resolution of such disputes becomes crucial to the efficacy of international arbitration as a system of dispute resolution. The present book provides a comparative analysis of the practice of three carefully selected legal orders: the English, German and Swiss and outlines possible ways forward. As the work strikes a balance between theory and practice, it will appeal to practitioners, researchers, but also students looking to develop their understanding of the international arbitration field.